2003
DOI: 10.3346/jkms.2003.18.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Mutations of The Gene for Kir 1.1 (ROMK) in Antenatal Bartter Syndrome Presenting with Transient Hyperkalemia, Evolving to a Benign Course

Abstract: Bartter-like syndrome encompasses a set of inherited renal tubular disorders associated with hypokalemic metabolic alkalosis, renal salt wasting, hyperreninemic hyperaldosteronism, and normal blood pressure. Antenatal Bartter syndrome, a subtype of Bartter-like syndrome, is characterized by polyhydramnios, premature delivery, life-threatening episodes of fever and dehydration during the early weeks of life, growth retardation, hypercalciuria, and early-onset nephrocalcinosis. Mutations in the bumetanide-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
8
0
4
Order By: Relevance
“…6). Transient neonatal hyperkalemia with salt wasting, hyponatremia, and hyporeninemic hyperaldosteronism, mimicking pseudohypoaldosteronism type 1, has been seen in some individuals with ROMK Bartter's syndrome (81,148). This transient hyperkalemic phenotype is consistent with the role of ROMK in forming the 35-pS K ϩ channels in both TAL and principal cells.…”
Section: Bartter's Syndrome: a Tal Tubulopathymentioning
confidence: 98%
“…6). Transient neonatal hyperkalemia with salt wasting, hyponatremia, and hyporeninemic hyperaldosteronism, mimicking pseudohypoaldosteronism type 1, has been seen in some individuals with ROMK Bartter's syndrome (81,148). This transient hyperkalemic phenotype is consistent with the role of ROMK in forming the 35-pS K ϩ channels in both TAL and principal cells.…”
Section: Bartter's Syndrome: a Tal Tubulopathymentioning
confidence: 98%
“…KCNJ1 mutation could lead to antenatal Bartter syndrome, which is characterized by hypokalemic alkalosis, hypercalciuria, salt wasting, and low blood pressure [12][13][14][15]. In Karnes's study on African-American showed that KCNJ1 single nucleotide polymorphisms (SNPs) and haplotypes are associated with thiazide-induced dysglycemia and new onset diabetes (strongest association: OR=2.14) [16].…”
Section: Introductionmentioning
confidence: 98%
“…Mutational analysis of the KCNJ1 gene revealed novel mutation. Cho and GuayWoodford [6] also reported a baby who mimicked pesudohypoaldosteronism in the neonatal period; a correct diagnosis was established after detection of mutation in the ROMK.…”
Section: Discussionmentioning
confidence: 96%